Electrochemical dithiothreitol assay for large-scale particulate matter studies. Issue 3 (4th March 2019) - Berg, Kathleen E.; Turner, Laurelle R.; Benka-Coker, Megan L.; Rajkumar, Sarah; Young, Bonnie N.; Peel, Jennifer L.; Clark, Maggie L.; Volckens, John; Henry, Charles S.
Abstract: Particulate matter (PM) air pollution is associated with human morbidity and mortality. Measuring PM oxidative potential has been shown to provide a predictive measurement between PM exposure and adverse health impacts. The dithiothreitol (DTT) assay is commonly used to measure the oxidative potential of PM2.5 (PM less than 2.5 µm aerodynamic diameter). In the common, kinetic form of this assay, the decay of DTT is quantified over time (indirectly) using 5, 5′-dithiobis(2-nitrobenzoic acid) (DTNB, Ellman's reagent) via UV/vis absorbance spectroscopy. The loss of DTT can also be quantified directly using electrochemical detection. The objectives of this work were (1) to evaluate the electrochemical assay, using commercially available equipment, relative to the UV/vis absorbance assay and (2) to apply the electrochemical method to a large (>100) number of PM2.5 filter samples. Also presented here is the comparison of an endpoint assay to the kinetic assay, in an attempt to reduce the time, labor, and materials necessary to quantify PM oxidative potential. The endpoint, electrochemical assay gave comparable results to the UV/vis absorbance assay for PM2.5 filter sample analysis. Finally, high filter mass loadings (higher than about 0.5 µg PM per mm 2 filter) lead to suboptimal DTT assay performance, which suggests future studies should limit particle mass loadings on filters. Copyright © 2019 American Association for Aerosol Research